Gamification in Higher Education - Kovácsné Pusztai, Kinga (Teaching Mathematics and Computer Science, 2021)
The way of thinking and the way of life of the today’s children and teenagers have changed radically. Some of the well-established pedagogical methods that were used for decades have become obsolete. Therefore, we need to look for a new method to approach Generations Z and Alpha. Gamification, which has been known since 2010 and means the use of game elements in other areas of life, offers an opportunity to do so. In addition to a brief description of gamification, my article shows some possibilities for using it at the university. Furthermore, I investigate the impact of gamification on the student in "Algorithms and Data Structures" university course. Subject Classification: 97P30